Aluminum-Immobilizing Rhizobacteria Modulate Root Exudation and Nutrient Uptake and Increase Aluminum Tolerance of Pea Mutant E107 (brz) - Andrey A. Belimov; Alexander I. Shaposhnikov; Tatiana S. Azarova; Oleg S. Yuzikhin; Edgar A. Sekste; Vera I. Safronova; Igor A. Tikhonovich (Plants, 2023)
It is well known that plant-growth-promoting rhizobacteria (PGPRs) increase the tolerance of plants to abiotic stresses; however, the counteraction of Al toxicity has received little attention. The effects of specially selected Al-tolerant and Al-immobilizing microorganisms were investigated using pea cultivar Sparkle and its Al-sensitive mutant E107 (brz). The strain Cupriavidus sp. D39 was the most-efficient in the growth promotion of hydroponically grown peas treated with 80 µM AlCl3, increasing the plant biomass of Sparkle by 20% and of E107 (brz) by two-times. This strain immobilized Al in the nutrient solution and decreased its concentration in E107 (brz) roots. The mutant showed upregulated exudation of organic acids, amino acids, and sugars in the absence or presence of Al as compared with Sparkle, and in most cases, the Al treatment stimulated exudation. Bacteria utilized root exudates and more actively colonized the root surface of E107 (brz). The exudation of tryptophan and the production of IAA by Cupriavidus sp. D39 in the root zone of the Al-treated mutant were observed. Aluminum disturbed the concentrations of nutrients in plants, but inoculation with Cupriavidus sp. D39 partially restored such negative effects. Thus, the E107 (brz) mutant is a useful tool for studying the mechanisms of plant–microbe interactions, and PGPR plays an important role in protecting plants against Al toxicity.